Peer reviewers identified spin in manuscripts of nonrandomized studies assessing therapeutic interventions, but their impact on spin in abstract conclusions was limited - Lazarus, C; Haneef, R; Ravaud, P; Hopewell, S; Altman, D; Boutron, I (Elsevier, 2016)
Objective Spin is defined as a specific way of reporting, whether intentional or unintentional, to emphasize that the beneficial effect of the intervention is greater than that shown by the results. Our aim was to describe the spin identified, deleted or added by peer reviewers in reports of non-randomized studies assessing a therapeutic intervention and to evaluate the prevalence of spin in the abstract conclusions that peer reviewers failed to identify. Design Systematic review and retrospective before–after study. Sample All primary reports of non-randomized studies assessing a therapeutic intervention (n=128) published in BioMed Central Medical Series journals between January 1, 2011 and December 31, 2013. Main Outcome Measures Number and type of spin examples identified, deleted or added by peer reviewers in the whole manuscript. Number of reports with spin in abstract conclusions not detected by peer reviewers. The level of spin (i.e., no, low, moderate and high level of spin) in the abstract conclusions before and after the peer review. Results For 70 (55%) submitted manuscripts, peer reviewers identified at least one example of spin. Of 123 unique examples of spin identified by peer reviewers, 82 (67%) were completely deleted by the authors, 20 (16%) partially deleted and 21 (17%) not removed in the final published article. For19 articles (15%), peer reviewers requested adding some spin, and for 11 (9%), the spin was added by the authors. Peer reviewers failed to identify spin in abstract conclusions of 97 (76%) reports. The most prevalent example of spin in the abstract conclusions related to the use of causal language, was identified in 64 (50.0%) published abstract conclusions both before and after the peer review. The level of spin in the abstract conclusion increased in 8 articles (6%), decreased in 15 (12%), and remained unchanged in 105 (82%). Conclusion Peer reviewers identified many examples of spin in submitted manuscripts. However, their influence on change of spin in the conclusion was low. This is now added in the conclusion